Inflammatory and vascular biomarkers as predictors of all‐cause death and cardiovascular outcomes in an Australian community‐based cohort - Silvia Lee; Alison Castley; Matthew Knuiman; David Nolan; Frank Sanfilippo; Girish Dwivedi (Physiological Reports)
Abstract Biomarkers that identify individuals who are at higher risk of cardiovascular outcomes will allow for early intervention, lowering the incidence of adverse outcomes. This study investigated whether circulating levels of GDF‐15, E‐selectin, CD14, and ST2 are predictors of death and cardiovascular outcomes in 981 individuals who did not have a history of cardiovascular disease (CVD) during follow‐up periods of 5, 10, and 20 years. During the 20‐year follow‐up, there were 389 deaths (including 147 from CVD), 105 participants had acute coronary syndrome (ACS), and 467 people had major adverse coronary and cerebrovascular events (MACCE) (including all‐cause death). In the fully adjusted model, sE‐selectin (5‐year HR, 3.03; 95% CI 1.31–7.01), sCD14 (5 years 3.11; 1.02–9.45 and 10 years 2.52; 1.23–5.16), and sGDF‐15 (10 years 2.07; 1.13–3.78 and 20 years 1.79; 1.24–2.56) predicted all‐cause death. sE‐selectin (5 years 2.19; 1.13–4.26), sCD14 (10 years 2.00; 1.08–3.68), and sGDF‐15 (10 years 1.95; 1.18–3.22 and 20 years 1.53; 1.11–2.12) predicted MACCE. sGDF‐15 predicted ACS at 5 (4.44; 1.01–19.49), 10 (2.86; 1.08–7.57) and 20 years (2.57; 1.31–5.04). High serum levels of sE‐selectin, sGDF‐15, and sCD14 at baseline are important independent risk factors for all‐cause death and cardiovascular outcomes in a population without prevalent CVD.